Erratum: Tingkat Kondisi Fisik Atlet Bolabasket PPLOP Jawa Tengah Ditentukan dengan Tes dan Pengukuran Khusus - Agam Akhmad Syaukani; Nur Subekti; Eko Sudarmanto (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.779 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.